IoT-Based Fire Safety System Using MQTT Communication Protocol - See , Yuen Chark; Ho , En Xiang (International Journal of Integrated Engineering, 2020)
Fire can be made useful for various purposes. However, uncontrollable fire may result in property damage and human death. The major factor of fire deaths is due to excessive smoke inhalation. Therefore, early detection of fire is crucial in fire detection systems. The conventional fire detection system does not come with a false alarm prevention system. Besides, the system is unable to tell the exact location of the fire. In this project, an Internet of Things (IoT) based fire safety system is developed to overcome these problems. The proposed system consists of three major parts which are the detector, processing unit and surveillance. The detector unit is an integration of ESP32, carbon monoxide sensor, ionization smoke detector, buzzer, temperature and humidity sensor. As the processing unit, Raspberry Pi is used to run the Node-RED application, which processes the data and performs monitoring. The communication between the detector and processing unit is based on the Message Queuing Telemetry Transport (MQTT) protocol. A surveillance unit is where a camera is installed to monitor the condition of the surrounding. The response of the system is based upon the sensor’s values or the user’s response. Once the fire breakout is confirmed, the system will immediately sound the alarm, and Global Positioning System (GPS) coordinates and floor plan of the accommodation will send to the nearby fire station. The floor plan is developed to track the exact location of the fire. Experiments are carried out on the proposed fire safety system, and encouraging results are produced.